2000
DOI: 10.1111/j.1365-2621.2000.tb15999.x
|View full text |Cite
|
Sign up to set email alerts
|

Pastry Lift and Croissant Volume as Affected by Microbial Transglutaminase

Abstract: Microbial transglutaminase forms nondisulfide covalent crosslinks in proteins and is increasingly being used in foods. We have previously demonstrated beneficial effects of microbial transglutaminase during breadmaking, which are comparable to traditional oxidizing improvers, hypothesized to act via formation of disulfide crosslinks. Transglutaminase substantially improved the lift of puff pastry. It also had a dramatic effect on the volume of yeasted croissants made with both white flour and a blend of wholem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 3 publications
2
46
1
3
Order By: Relevance
“…From the above-indicated findings it follows that: (i) considering the product cambering, TGM has the best effect after the first day of freezing of dough, which can follow from the necessity that the dough needs some time for its activation (this knowledge is corresponding to data reported by Gerrard et al [13]); (ii) freezing leads to the diminution of the size of pastry, which is in all probability caused by a decrease of the yeast activtiy due to freezing; (iii) the sensory quality of pastry decreased in all samples with extending the length of storage; however, in the case of samples with the addition of TGM the evaluation was higher than in the case of control before and after freezing; (iv) the best effect on the cambering of dough as well as on the sensory evaluation was exerted at the concentration of 4.5 mg TGM/300 g flour; (v) the dough at the concentration of 7.5 mg TGM/300 g flour was very adhesive and therefore its processing was difficult. The initial adhesive power was later on partially reduced during its further development, which is also in agreement with literature data [12]; (vi) freezing induced the marbling of pastry, which met with an unfavourable response of assessors.…”
Section: Pastry With Tgmsupporting
confidence: 73%
See 1 more Smart Citation
“…From the above-indicated findings it follows that: (i) considering the product cambering, TGM has the best effect after the first day of freezing of dough, which can follow from the necessity that the dough needs some time for its activation (this knowledge is corresponding to data reported by Gerrard et al [13]); (ii) freezing leads to the diminution of the size of pastry, which is in all probability caused by a decrease of the yeast activtiy due to freezing; (iii) the sensory quality of pastry decreased in all samples with extending the length of storage; however, in the case of samples with the addition of TGM the evaluation was higher than in the case of control before and after freezing; (iv) the best effect on the cambering of dough as well as on the sensory evaluation was exerted at the concentration of 4.5 mg TGM/300 g flour; (v) the dough at the concentration of 7.5 mg TGM/300 g flour was very adhesive and therefore its processing was difficult. The initial adhesive power was later on partially reduced during its further development, which is also in agreement with literature data [12]; (vi) freezing induced the marbling of pastry, which met with an unfavourable response of assessors.…”
Section: Pastry With Tgmsupporting
confidence: 73%
“…The best results of raising the dough have been achieved by the addition of transglutaminase (5000 ppm) to the subsequently frozen dough (activation of enzymes during defreezing). The positive effect of the addition of transglutaminase persisted even during the 90-day storage of frozen pastry and the bread crumb showed to be better than in the control [12,13].…”
Section: Introductionmentioning
confidence: 55%
“…Sakamoto et al [4] reported that physical properties of Chinese noodles could be improved by the addition of microbial TG. Dramatic improving effects of TG on yeasted croissant volume and lift of puff pastry were also reported [5]. Investigations on the effects of TG on empirical rheological properties (e.g., farinograph, extensigraph) and bread quality are even fewer.…”
Section: Introductionmentioning
confidence: 95%
“…(80,81) Other additives, very useful in frozen dough, are the hydrocolloids for their water retention capacity that improves the stability during frozen storage. (28) In the conventional processes the hydrocolloids improve dough stability during proofing, (83) and impart a softening effect of the crumb extending the shelf life of the baked breads.…”
mentioning
confidence: 99%